Impacts of long-term international volunteering on volunteers’ intercultural competence - McKivison, Lacey (2018)
Intercultural competence has become an extremely important skill for one to have in today’s globally-connected world. As intercultural competence is something that must be developed over time, it is therefore crucial to understand how one develops intercultural competence, and the impact that such developments have on an individual. Immersion experiences in particular have been proven to have the ability to help aid in intercultural competence development, and one specific context that has not been studied much in intercultural competence research is long-term international volunteering, which research has shown has the unique elements needed to foster intercultural competence development.